Application of small extracellular vesicles in the diagnosis and prognosis of nasopharyngeal carcinoma - Zhang, Jiali; Huang, Defa; Lan, Xianbin; Deng, Dongming; Li, Jijing; Zhang, Dongzhi; Li, Yue; Zhong, Tianyu; Peng, Shaoping (Frontiers in Cell and Developmental Biology, 2023)
Nasopharyngeal carcinoma (NPC) is a malignant tumor originating from the epithelium of the nasopharynx. The disease is insidious and most patients are diagnosed at the advanced stage with a poor prognosis. Early diagnosis is an important measure to reduce NPC mortality. Small extracellular vesicles (sEVs) are rich in a variety of bioactive molecules such as proteins, nucleic acids and lipids, which can participate in the physiological and pathological regulation of the body by affecting the function of target cells. Numerous studies have shown that some RNAs and proteins in sEVs of tumor origin have a key role in the development of nasopharyngeal carcinoma and are potential candidates for malignancy detection. Studying the relationship between these sEVs cargos and NPC may help in the diagnosis of the disease. Here, we summarized the important role of sEVs as biomarkers in the diagnosis of nasopharyngeal carcinoma and their application in NPC metastasis and prognosis. In addition, we discuss the promise and limitations of sEVs as a biomarkers.